Study and Analysis of the Affecting Factors on the Pedestrians' Movement in the City Streets (The Situation in the Maghreb Arabi Street in Lattakia) - رستم, أكرم; شاهين, براعم (Latakia University Journal -Engineering Sciences Series, 2021)
The aim of the research study the reality of pedestrian traffic in the streets of Syrian cities, and their own processing of the piers and, in addition to evaluating the performance of these fittings for the purpose of detection of the existing defects, and reach optimum functioning of the not. Identified street of the Maghreb in the city of Latakia as a study enjoy being the density of traffic is high, where the territory was divided into sectors to know the number of pedestrians in the peak hour day and bring them to the categories as (age, gender) and measure the speed and time of movement of the pedestrian in each category of each sector, where the use of survey method the field survey in addition to the application of the methodology HCM2010 own the streets of the urban and to assess the level of performance of the service problem. The results of the field survey for the study area during several months, the presence of occupancies, many on the pavements by the shops, adding to the Rovers, and the other with a defect in the construction of the pier, and that the planting of trees is appropriate in terms of type and manner of expansion of the root, and having a hole different as a result of phone and other negatively impacted on the sidewalks, and pedestrian traffic and their speed. The study also showed that the assessment of the pedestrian traffic using the HCM2010 did not take into account the good design the paving of sidewalk, but relied on specific criteria including the age, the gender, the space allocated to them.